Non-Hermitian chiral skin effect - Xin-Ran Ma; Kui Cao; Xiao-Ran Wang; Zheng Wei; Qian Du; Su-Peng Kou (Physical Review Research, 2024)
The interplay between non-Hermitian effects and topological insulators has become a frontier of research in non-Hermitian physics. However, the existence of a non-Hermitian skin effect for topological-protected edge states remains controversial. In this paper, we discover a new type of the non-Hermitian skin effect called the non-Hermitian chiral skin effect. Non-Hermitian chiral skin effect is induced by inhomogeneous edge dissipation under closed boundary conditions. In particular, the chiral modes of the non-Hermitian chiral skin effect localize around “topological defects” characterized by global dissipation rather than being confined to the system boundaries. We show its detailed physical properties by taking the non-Hermitian Haldane model as an example. As a result, the intrinsic mechanism of the hybrid skin-topological effect in Chern insulators is fully understood via the non-Hermitian chiral skin effect. Therefore this work will be helpful for the research on both non-Hermitian physics and topological quantum states.